Association between miRNAs expression and cognitive performances of Pediatric Multiple Sclerosis patients: A pilot study. Issue 2 (17th January 2019) - Liguori, Maria; Nuzziello, Nicoletta; Simone, Marta; Amoroso, Nicola; Viterbo, Rosa Gemma; Tangaro, Sabina; Consiglio, Arianna; Giordano, Paola; Bellotti, Roberto; Trojano, Maria
Abstract: Introduction : The Pediatric onset of Multiple Sclerosis (PedMS) occurs in up to 10% of all cases. Cognitive impairment is one of the frequent symptoms, exerting severe impact in patients' quality of life and school performances. The underlying pathogenic mechanisms are not fully understood, and molecular markers predictive of cognitive dysfunctions need to be identified. On these grounds, we searched for molecular signature/s (i.e., miRNAs and target genes) associated with cognitive impairment in a selected population of PedMS patients. Additionally, changes of their regional brain volumes associated with the miRNAs of interest were investigated. Methods: Nineteen PedMS subjects received a full cognitive evaluation; total RNA from peripheral blood samples was processed by next‐generation sequencing followed by a bioinformatics/biostatistics analysis. Results: The expression of 11 miRNAs significantly correlated with the scores obtained at different cognitive tests; among the others, eight miRNAs correlated with the Trail Making Tests. The computational target prediction identified 337 genes targeted by the miRNAs of interest; a tangled network of molecular connections was hypothesized, where genes like BST1, NTNG2, SPTB, and STAB1, already associated with cognitive dysfunctions, were nodes of the net. Furthermore, the expression of some miRNAs significantly correlated with cerebral volumes, for example, four miRNAs with the cerebellum cortex. Conclusions: As far as we know, this is the first evaluation exploring miRNAs in the cognitive performances of PedMS. Although none of these results survived the multiple tests' corrections, we believe that they may represent a step forward the identification of biomarkers useful for monitoring and targeting the onset/progression of cognitive impairments in MS. Abstract : Based on several published evidences on the occurrence of cognitive impairment during MS, the main aim of this investigation was to suggest novel molecular hypothesis that may sustain the onset of these disabling symptoms, as well as they may cause changes in the regional brain volumes of MS patients. We believe that the potential of our research will be useful also for the clinical practice.